1982
DOI: 10.1111/j.1471-4159.1982.tb12540.x
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of 2′,3′‐Cyclic Nucleotide 3′‐Phosphodiesterase in Rat Tissues

Abstract: The activity of the myelin-associated enzyme 2',3'-cyclic nucleotide 3'-phosphodiesterase (CNP) was measured in 14 rat tissues and in subcellular fractions of rat liver by a sensitive fluorometric method, using cyclic NADP as substrate. CNP activity in brain (339 mumol/h/mg protein) was fourfold that of the sciatic nerve. The activities in tissues outside the nervous system ranged from a low of 0.42 mumol/h/mg protein in the unwashed red blood cell to a high of 9.96 in the spleen. The activity was highest in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…It is suggested that CNP has a role in morphological changes of cells through modulation of the cytoskeleton, because the activity of CNP is relatively high in tissues containing cells with membranes capable of undergoing transformation and elaboration such as spleen and thymus (Weissbarth et al, 1981), and because CNP induces profound morphological changes in nonneural cells when expressed ectopically (Staugaitis et al, 1990;De Angelis and Braun, 1994). Our finding that CNP is expressed in the early stage of morphological differentiation compromises well with this suggested role.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is suggested that CNP has a role in morphological changes of cells through modulation of the cytoskeleton, because the activity of CNP is relatively high in tissues containing cells with membranes capable of undergoing transformation and elaboration such as spleen and thymus (Weissbarth et al, 1981), and because CNP induces profound morphological changes in nonneural cells when expressed ectopically (Staugaitis et al, 1990;De Angelis and Braun, 1994). Our finding that CNP is expressed in the early stage of morphological differentiation compromises well with this suggested role.…”
Section: Discussionsupporting
confidence: 70%
“…In addition to myelinating cells such as oligodendrocytes and Schwann cells, CNP is also expressed in various cell types such as chromaffin cell culNonspecific association of 2',3'-cyclic nucleotide 3'-phosphodiesterase with the rat forebrain postsynaptic density fraction tures (McFerran and Burgoyne, 1997), lymphocytes and retinal cells (Uyemura et al, 1972;Giulian and Moore, 1980;Weissbarth et al, 1981;Vogel and Thompson, 1988), liver cells (Dreiling et al, 1981), FRTL-5 thyroid cells (Laezza et al, 1997;Bifulco et al, 2002), and muscle cells (Weissbarth et al, 1981), indicating more general cellular functions. Recently, we found that CNP is expressed in Purkinje cells (PC's) and unidentified PSD95-positive cells but not in granule cells (GC's) in cerebellar cell cultures, indicating that both CNP is expressed in some subpopulations of cerebellar cells in addition to OL (Cho et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2Ј,3Ј-Cyclic Nucleotide 3Ј-Phosphodiesterase (CNPase) AssayCNPase was measured using the coupled enzyme method of Weissbarth et al (70). Samples (20 l) were incubated for 20 min at 30°C with 4 mM cyclic NADP, 2 mM D-glucose 6-phosphate, 1 unit of glucose 6-phosphate dehydrogenase, and 0.025% Triton X-100 in 0.2 M MES buffer, pH 6.0, in a total volume of 100 l. The reaction was stopped by adding 2 ml of 50 mM NaCO 3 , pH 10.5, and the fluorescence of the resulting NADPH was measured (ex ϭ 360, em ϭ 460 nm).…”
Section: Methodsmentioning
confidence: 99%
“…CNP is associated exclusively with these glial cells in the nervous system, and constitutes 4% of the total myelin proteins in the central nervous system; it is also present at lower levels in photoreceptor cells and several nonneural cells, notably lymphocytes (3,4). In oligodendrocytes, this enzyme is found throughout the cell body but is much more abundant within the process extensions, as well as in the outer cell periphery, in close apposition to the plasma membrane (5,6).…”
mentioning
confidence: 99%